Analisis Omnibus Law Tentang Kesehatan Dalam Kasus Malpraktik Medik - Made Arya Duta Gunaksara; I Made Minggu Widyantara; Ni Made Sukaryati Karma (Jurnal Preferensi Hukum, 2025)
Medical malpractice is an act that can harm patients and the wider community, malpractice can occur anywhere, therefore, it is important to know how to prevent and what the liability is. The problems formulated in this thesis research are How is the legal regulation of the Omnibus Law on Health in efforts to prevent medical malpractice and How is legal liability for perpetrators of malpractice. This research uses normative legal research methods, with the type of legislative approach and literature study. The results showed that the prevention of malpractice can be seen through the obligations of medical personnel, the rights of patients and the standardization of the profession itself. We can take medical malpractice liability through ethical malpractice, and juridical malpractice, where juridical includes criminal, civil, and administrative.